(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
In this work are analyzed the carabidocaenosis found by means of pitfall traps in some appie orchards in Valtellina valley. The whole fauna seems to indicate a certain similarity with that typical of the cultivated fields in Centrai Europe, but some elements of the Po valley are present too. The application of two ecological indexes (Scerensen and Renkonen) showed that the different paedological and rnicroclimatical conditions of the fields deterrnine distinct associations. The possible role of ground beetles as predators of appie orchard pests is discussed.